The Needs Analysis of the Electronic Student Worksheets (e-LKPD) Based on Discovery Learning for the Topic of Traveling Waves in High School - Khotami, Muhamad Habil; Marlina, Leni; wiyono, Ketang (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This research is research on developing the ADDIE model at the analysis stage. A needs analysis is needed to identify the character profile of learners. This research was conducted at SMA Sriguna Palembang with correspondence of 36 students. The questionnaire of needs analysis questions in this study was disseminated through the Google form platform. The teaching materials developed are in the form of e-LKPD. The analysis results of using other learning resources, such as e-LKPD, as many as 58.3% are still hesitant to use it. Walking wave material raised in this study showed that 55.6% agreed that the material was difficult. The learning model used by the Discovery Learning model. The results of the analysis of the application of discovery learning in physics learning, as many as 44.4% are still hesitant to make observations or experiments on physics material, as many as 50% are still hesitant to analyze the results of observations or experiments, as many as 63.9% are still hesitant to find new things from the results of observations or experiments that have been done. The development of e-LKPD is expected to facilitate students' learning, especially wave material with the discovery Learning model. This research can be used as an initial overview or reference for further development research.